Xanthogranulomatous cholecystitis shows overlapping histological features with IgG4‐related cholecystitis. Issue 4 (14th December 2017) - Hong, Soon Auck; Sung, You‐Na; Kim, Hyoung Jung; Lee, Sang Soo; Lee, Jae Hoon; Ahn, Chul‐Soo; Hwang, Shin; Yu, Eunsil; Zen, Yoh; Kim, Myung‐Hwan; Hong, Seung‐Mo
Abstract : Aims: Xanthogranulomatous cholecystitis (XGC), an unusual histological variant of chronic cholecystitis, is characterised by mixed foamy histiocytic and lymphoplasmocytic infiltration and fibrosis. Radiologically, the poorly defined nodular growth pattern often leads to the misinterpretation of XGC as gallbladder cancer. In this study, we aimed to identify the relationship of XGC with IgG4‐related cholecystitis. Methods and results: We re‐evaluated 57 surgically resected XGCs and 104 conventional chronic cholecystitis cases, according to the histological features observed in IgG4‐related disease, including lymphoplasmocytic infiltration, storiform fibrosis, obliterative phlebitis, and IgG4‐positive plasma cells. XGCs contained a significantly increased mean number of IgG4‐positive plasma cells [34.8/high‐power field (HPF)] as compared with conventional chronic cholecystitis (4.8/HPF; P <  0.001), and 16 XGCs (28%) harboured >50 IgG4‐positive cells per HPF. Nine XGCs (16%), including one case with IgG4‐related autoimmune pancreatitis, showed 'the histological features suggestive of IgG4‐related disease', as described in the consensus statement regarding this condition. Extracholecystic inflammatory extension (seven cases, P  = 0.009) and mass‐forming lesions (eight cases, P  < 0.001) were more frequently seen in XGC cases with histological features suggestive of IgG4‐related disease than in cases without those microscopic changes. Conclusions: XGCs with IgG4‐positive cell infiltration are considered to be mimickers, as xanthogranulomatous inflammation generally contradicts a diagnosis of IgG4‐related disease and is weakly associated with other typical organ manifestations of IgG4‐related disease. However, XGC may be a concurrent condition, particularly in patients with IgG4‐related disease in other organs.